The Australian Hydrographic Information System - Halls, Ian W.; Furness, Ronald A. (The International Hydrographic Review, 2015)
The rapid changes in technology created by both the electronic and information ages have generated tremendous forces on the style and procedures of managing electronic hydrographic data acquisition and processing. This technological force is shaping the future direction for hydrographic information management within the Royal Australian Navy (RAN) Hydrographic Office. This paper examines the concept of the RAN Hydrographic Office Hydrographic Information System (HIS) and, in particular, addresses the need for the HIS to be a system undergoing continual development to maintain pace with technological advancement.